Smart Umbrella / Norazman Harun … [et al.] - Harun, Norazman; Mohd Rozainal, Anaqi Nu'aim; Samsuri, Imran Hakim; Abdul Rahim, Mohammad Syazwan Hifzhan; Azman, Muhammad Amirul Edwan; Othman, Muhammad Redzuan (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
Navigating through unpredictable weather poses a significant challenge for individuals with visual impairments, often leaving them uncertain about whether to bring an umbrella when venturing outdoors. In response to this pressing need, a groundbreaking solution is proposed: the Smart Umbrella. Specifically designed for individuals with visual impairments, this innovative device integrates cutting-edge sensor technologies and intelligent assistance systems to enhance both mobility and safety in adverse weather conditions.